Early versus late inpatient awake transcervical injection laryngoplasty after thoracic aortic repair. (8th July 2017) - Chen, Diane W.; Price, Matt D.; LeMaire, Scott A.; Coselli, Joseph S.; Liou, N. Eddie; Ongkasuwan, Julina
Abstract : Background: Vocal fold movement impairment (VFMI), a known complication following thoracic aortic surgery, has been associated with poorer surgical outcomes, including higher pulmonary complications and longer length of stay (LOS). Awake transcervical injection laryngoplasty in the inpatient setting serves to augment pulmonary toilet function for affected patients. This study investigates clinical outcomes of patients who underwent early versus late injection laryngoplasty following aortic surgery. Methods: A 5‐year review (2011–2016) of 35 patients who underwent inpatient injection laryngoplasty for VFMI following aortic repair was conducted. Data included demographics, surgery parameters, laryngologic evaluation, pulmonary complications, LOS, and mortality. Early injection was defined as within 5 days from extubation. Statistical analyses were performed using SPSS, version 17.0 (IBM Corp., Armonk, NY). Results: All 35 patients (mean age 56, 77% male) underwent left vocal‐fold injection laryngoplasty without complication. There were 15 (43%) early procedures and 20 (57%) late procedures. Mean LOS for early and late injection groups (13 vs. 20 days, respectively) significantly differed ( P  = 0.04, 95% confidence interval (CI) 0.3 to 14.4). Early laryngoplasty cohorts experienced less pulmonary complications (20%) than those who had late medialization (50%), but this did not reach significance ( P  = 0.06, 95% CI −0.3 to 8.1). The most common complication type in both groups was therapeutic bronchoscopy. Conclusion: Early awake injection laryngoplasty within 5 days from extubation is feasible and may improve clinical outcomes for patients with VFMI following aortic repair. Further prospective studies on this approach for VFMI after thoracic surgery are needed. Level of Evidence: 4. Laryngoscope, 128:144–147, 2018